MENGHITUNG SPECIFIC ENERGY CONSUMPTION (SEC) PADA ALAT ROTARY KILN DI PABRIK 2 PT SEMEN BATURAJA Tbk. - Sriwijaya, Wahyu; Safaruddin, Safaruddin; Muzzaki, Mukti Mabrur (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2023)
This study aims to calculate the specific energy consumption (SEC) in the rotary kiln in the cement production process. This research method involves collecting rotary kiln operational data from cement factories over a certain period. The results show that SEC can vary significantly depending on factors such as feedstock type, equipment thermal efficiency, and operational settings. These factors can contribute to SEC fluctuations which can affect the overall efficiency of the cement production process. Therefore, an in-depth understanding of how these factors interact with each other is essential to optimize energy use in cement production. This study provides insight into how to measure and calculate SEC in the context of rotary kilns in the cement industry. With a better understanding of the main contributors to energy consumption in these processes, cement manufacturers can identify opportunities to reduce SEC through increasing thermal efficiency, selecting more suitable raw materials, and optimizing operational arrangements